Design of a Versatile and Rapid Calculator for Oncological Computations - Dinçkal, Ç.; Dinçkal, Çiğdem (Nova Science Publishers, Inc., 2019)
In oncology, there exists many complicated and time-consuming computations for students, clinicians and medical researchers. Although many programs generated in Microsoft Excel have been studied many times, the improvements in design of programs are still an issue of concern. So design of calculator becomes essential for practical use. The objective of this study is to design a rapid and versatile calculator named as TGTSCalculator in Microsoft Excel for comprehensive computation of clonogenic cells amount when growth and irradiation for tumor occurred for all tumor growth models and the total amount of relative cells outliving the treatment schedule (in other words; survival fraction) after radiotherapy. Microsoft Excel with Visual Basics for Applications (VBA) has been employed since it is a high versatile and extensively used special spreadsheet program and easily accessible and available for biomedical scientists and clinicians for a wide range of applications. TGTSCalculator is so transparent and practical that any kind of users requires only requires clicking its macro or CALCULATE button in spreadsheet to manage the all computations effectively and simultaneously. © 2020 by Nova Science Publishers, Inc. All rights reserved.
Design of a Versatile and Rapid Calculator for Oncological Computations
Keywords: Clonogenic Survival Fraction; Microsoft Excel; Treatment Schedule; Tumor Growth Models; Visual Basics For Applications